Quaternary Segmentation Characteristics of the Hunhe Fault, Northeast China - Bo Wan; Guanghao Ha; Xiaohui Zhao; Rui Suo (Applied Sciences)
The northern segment of the Tanlu fault zone, which encompasses the Dunhua–Mishan and Yilan–Yitong fault zones, plays a critical role in the tectonic framework of Northeast China. This study focuses on the Hunhe fault, part of the Liaoning segment of the Dunhua–Mishan fault zone, which exhibits concealed characteristics and an NE–NEE orientation. We employ remote sensing and field investigations to accurately delineate the Hunhe fault’s location, scale, and tectonic activity. The findings indicate that the Hunhe fault displays significant spatial variability in tectonic activity. Some segments show evidence of late Quaternary activity, contradicting prior research that classified the Hunhe fault as an active fault during the MIS (Marine Isotope Stages) 20-103MIS 20-103- MIS6-19MIS6-19 period and assessed its seismic potential differently. Recent field investigations suggest considerable spatial variability in tectonic activity, indicating segmental characteristics. In this study, the Hunhe fault is divided into segments based on five aspects: the fault structure and movement characteristics of the fault; transverse faults and obstruction structures; geological and geomorphological characteristics; seismic features; and fault activity. The detailed segments are as follows: the Shenyang segment, the Fushun segment, the Zhangdang-Nan Zamu segment, and the Nan Zamu to Ying Emeng East section. These findings aim to enhance the understanding of the seismic hazard potential associated with the Hunhe fault, highlighting the need for ongoing research to address its complexities and implications for regional seismic risk assessment.